Manajemen strategi untuk meningkatkan loyalitas nasabah di perbankan - A'yun, Qurrota (Maliki Interdisciplinary Journal, 2024)
The purpose of this study is to explore the importance of strategic management in increasing banking customer loyalty in Indonesia, amidst increasingly fierce competition in the banking industry. Banking is an important part of people's lives, and banks must be able to retain customers while attracting new ones. In this article, qualitative analysis is used through a literature review approach. By analyzing several articles on strategies to increase customer loyalty, the author found relevant discussions. The results show that including SWOT Analysis, Relationship Marketing, Customer Relationship Management (CRM), Cross-Selling, and Corporate Social Responsibility (CSR) can increase customer loyalty in banking. Through the implementation of these strategies, banks in Indonesia can build stronger long-term relationships with their customers.